An introduction to data analysis : quantitative, qualitative and mixed methods - Bergin, Tiffany (London : SAGE Publications, 2018)
Covering the general process of data analysis to finding, collecting, organizing, and presenting data, this book offers a complete introduction to the fundamentals of data analysis.
Includes bibliographical references (pages 243-262) and index.
Keywords: Mathematical analysis -- Data processing; Mathematical analysis -- Data processing fast; Mathematical analysis -- Data processing